MIDNIGHT SALE SEBAGAI SALAH SATU ELEMEN STRATEGI PROMOSI DALAM BISNIS RITEL - STEFANY, . (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The objective of this paper is to provide information relating to the promotion, particularly on the topic of â€œMidnight Sale as one element of the promotion strategy in the retail businessâ€. A large of sale made retailer strategies, one strategy that works is midnight sale. Findings from this study is that the midnight sale promotion strategies can contribute in increasing the sales turnover when the strategy is carried out correctly by the retailer. To be able to implement appropriate strategies, retailers must know the factors that need to be considered in the event held a midnight sale, including: service, quality products, discounts, security and convenience, advertising, personal selling, public relations, and promotions.